The Relationship Between Nutritional Status and Child Development Among Preschool Children Aged 3–6 Years - Sarah Faroja Krismawardani; Amin Zakaria; Musthika Wida Mashitah (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
Nutritional problems among preschool-aged children in Indonesia continue to show significant prevalence with potential impacts on children's cognitive, motor, language, and social development. This study aimed to analyze the relationship between nutritional status and development among preschool-aged children three to six years old at Posyandu Teratai, Wonorejo Village, Kencong District, Jember Regency. This study employed a descriptive analytical design with a cross-sectional approach conducted in October 2025. The study population consisted of all children aged three to six years registered in the Wonorejo Primary Health Center service area totaling 210 children, with a sample of 137 respondents selected using purposive sampling technique. Research instruments included digital scales and stadiometer to measure nutritional status based on Weight-for-Age index using WHO Antro standards with Z-score, and the Pre-Screening Development Questionnaire to assess child development. Data were analyzed using Chi-Square test with significance level α = 0.05. Results showed that most children had normal nutritional status (60.27%) and normal development (55.24%), with p-value 0.001 (p < 0.05) indicating a significant relationship between nutritional status and child development. Children with normal nutritional status showed a higher proportion of normal development compared to children with undernutrition or overnutrition, confirming the crucial role of adequate nutrition during the golden age period in supporting optimal development among preschool-aged children.